Maximum density effects on buoyancy-driven convection in a porous trapezoidal cavity - Varol, Yasin; Öztop, Hakan Fehmi; Pop, Ioan (Pergamon-Elsevier Science Ltd, 2010)
A numerical study of the steady buoyancy-induced flow and heat transfer in a trapezoidal cavity filled with a porous medium saturated with cold water at a temperature around 4 degrees C has been performed. The analysis has been done for a cavity with different aspect ratios ranging from 0.25 to 0.75 and Rayleigh numbers ranging from 100 to 1000 using a finite-difference method. It is found that four cells are formed inside the cavity independent of the Rayleigh number and aspect ratio. The existence of buoyancy force reversal resulting from the maximum density effect, leads to a reduction in the strength of the convective flow and also the average Nusselt number. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Maximum density; Natural convection; Trapezoidal enclosure; Porous media